Measuring the Maturity Level of Human Capital Management at Startup XYZ - Gultom, Naomi Theresia; Welly, John (Journal Integration of Social Studies and Business Development, 2023)
Startup XYZ, an Indonesian biotechnology start-up, specializes in producing environmentally friendly materials. The company primarily uses a business-to-business (B2B) model to sell its products. However, only one of their products significantly contributes to the company's revenue, indicating an issue regarding innovation performance. Innovation is generated through human capital, and effective human capital management (HCM) is essential for creating value, including innovation. This study aims to assess the level of HCM maturity at Startup XYZ and provide recommendations for its improvement. This study utilizes the HCM maturity framework developed by Bassi and McMurrer, which evaluates 5 drivers together with 23 practices of HCM. This study adopts a quantitative approach, utilizing an online questionnaire to collect data from 36 management employees of Startup XYZ. The findings reveal that Startup XYZ has a marginal level of HCM maturity, with 72.2% of respondents demonstrating an understanding of the company's HCM implementation. However, certain practices within each driver remain at a poor level, and 27.8% of respondents have a poor understanding of the company's HCM implementation. Therefore, the researcher recommends that Startup XYZ undertake rearrangement, investment, and evaluation to enhance HCM maturity. Additionally, improved communication about HCM implementation within the company is recommended to enhance HCM understanding among employees.